Different Catechol-O-Methyl Transferase Inhibitors in Parkinson's Disease: A Bayesian Network Meta-Analysis - Song, Zhaoming; Zhang, Jie; Xue, Tao; Yang, Yanbo; Wu, Da; Chen, Zhouqing; You, Wanchun; Wang, Zhong (Frontiers in Neurology, 2021)
Parkinson's disease (PD) is a common, chronic, progressive, debilitating neurodegenerative disease. The current levodopa treatment requires the addition of other drugs, such as catechol-O-methyl transferase (COMT) inhibitors, to alleviate motor fluctuations in advanced PD. Therefore, a theoretical reference for treatment is urgently needed. In this study, an appropriate search strategy was used to screen eligible studies on different drugs to treat patients with PD from the Embase, PubMed, and Cochrane Library. The publication dates were from January 1990 to June 2021. We integrated eligible randomized controlled trials, and statistical analysis was performed on three kinds of effectiveness outcomes and two types of safety outcomes. We assessed the average difference or odds ratio between each drug and placebo and summarized them as the average and 95% confidence interval (CI), respectively. In terms of efficacy, entacapone (mean difference [MD], 0.64 h; 95% CI, 0.29–1.0), opicapone (MD, 0.92 h; 95% CI, 0.35–1.5), and tolcapone (MD, 3.2 h; 95% CI, 2.1–4.2) increased patients' total ON-time compared to placebo. Tolcapone (MD, −100 mg; 95% CI −160 to −45) reduced the total daily dose of levodopa therapy. None of these three drugs was found to have statistical significance in mean change from baseline in UPDRS part III scores when compared with others. In terms of safety, tolcapone (MD, 3.8; 95% CI, 2.1–6.8), opicapone (MD, 3.7; 95% CI, 2–7.2), and entacapone (MD, 2.2; 95% CI, 1.5–3.3) increased the number of cases of dyskinesia compared to placebo. Entacapone (MD, 1.7; 95% CI, 1.3–2.2) and tolcapone (MD, 4.3; 95% CI, 1.3–15) were more likely to cause adverse events than placebo. In conclusion, opicapone showed higher efficiency and fewer safety problems in five indicators we selected when compared with the other two drugs.